Effects of the affordable care Act's Medicaid expansion on health insurance coverage for individuals in same‐sex couples. (11th January 2023) - Mann, Samuel; Carpenter, Christopher S.; Gonzales, Gilbert; Harrell, Benjamin; Deal, Cameron
Abstract: Objective: To examine whether the Affordable Care Act's (ACA's) Medicaid expansions affected health insurance coverage for individuals in same‐sex couples. Data Sources and Study Setting: We used data on adults aged 18–64 years in same‐sex couples ( n = 33, 512) from the 2008–2018 American Community Survey (ACS). Study Design: To estimate the effect of the impact of the state Medicaid expansions under the ACA on health insurance coverage for sexual minorities, we utilize a standard difference‐in‐differences approach to leverage the variation across geography and time in expanding Medicaid. Data Collection: Secondary and publicly available ACS data were obtained from IPUMS at the University of Minnesota. Principal Findings: We find that Medicaid expansion significantly increased health insurance coverage among low‐income men and women in same‐sex couples by 4.9 (standard error [ SE ] = 1.75) and 6.5 ( SE = 1.96) percentage points, respectively. We find increases in the likelihood of having Medicaid and reductions in private health insurance from an employer or privately purchased insurance. Effects on Medicaid take‐up are consistently larger for low‐income women in same‐sex couples as compared to low‐income men in same‐sex couples. Conclusions: We provide the first evidence on the relationship between state Medicaid expansions under the ACA and health insurance coverage among sexual minority adults, a group that has been understudied in past research. Our results confirm that sexual minority adults benefitted from the ACA's Medicaid expansions with respect to increased health insurance coverage.